Teaching general music : approaches, issues, and viewpoints - Abril, Carlos R., 1970-; Gault, Brent M. (Oxford University Press, 2016)
A variety of approaches to teaching general music influence music teaching and learning and inform the instructional practice of music educators. Although these approaches are valuable, problems arise when teachers choose to utilize a given approach without thoughtfully considering its role in the curriculum and its potential to meaningfully engage children in music learning. Important approaches to teaching general music must be understood, critically examined, and reimagined for their potential in school and community music education programs. 'Teaching General Music' brings together the top scholars and practitioners in general music education to create a panoramic view of general music pedagogy and to provide critical lenses through which to view these frameworks and practices.